TiO2 Based Photo Catalysts: Evidence for Electron Transfer by Iron - J. Shultz, Mary; Asong, Nkengafeh (Current Inorganic Chemistry (Discontinued), 2012)
Photocatalysts hold great potential for using sunlight to drive oxidations. Among photocatalysts, TiO2 is one of the most promising due to the strong oxidizing potential of the valence band; the strong oxidizing potential results in mineralization of a wide range of pollutants found in water. Developing a practical material requires improving the photo catalyst in two ways: narrowing the band gap and improving the quantum efficiency. Progress for improving TiO2 is hampered by apparently inconsistent literature reports for the effect of doping on efficiency. The basic source of the apparent inconsistencies is that charge transfer occurs at the catalyst surface and is thus affected by seemingly small differences in catalyst generation. This report contains results from 2.4 nm diameter particles; the small size results in improved consistency enabling comparison of modified and unmodified particles. Results suggest that batch-to-batch variation in grain boundaries and defects are a source of the apparent inconsistencies in the literature. The specific results reported here for iron doping support a model in which low-level iron doping enhances efficiency by acting as an electron transfer agent to molecular oxygen. Iron doping also modifies surface adsorption of methanol, the test molecule, and water. This contribution concludes with suggestions for future directions in developing iron-doped TiO2 photocatalysts.
Keywords: Charge transfer